The Effect of DEHY PRO (Dehydration Prevention) in Improving Preventive Behaviour among Parents toward Diarrhea Dehydration in Children Under Five - Lailil Fatkuriyah; Ainul Hidayati; Wike Rosalini (Jurnal Kesehatan dr. Soebandi, 2023)
The main cause of infant mortality in diarrhea is dehydration. Children under five are often brought to health services in deteriorating conditions to severe dehydration. Children under five deaths due to diarrhea are likely to be prevented if parents are able to recognize the signs of dehydration in children and take appropriate initial treatment when children have diarrhea. This study aims to determine the effect of the Dehy Pro application improves parents' behavior in preventing diarrhea dehydration in children under five. This study is a pre-experimental study with a one-group pre-posttest design. The research begins with the development of the Dehy Pro application through 4 stages: Define, Design, Develop, and Disseminate. Dehy Pro was introduced and used by 50 mothers with children under five in Karangrejo Village, Sumbersari-Jember District selected by using a purposive sampling technique. The independent variable of this study was the Dehy Pro application, meanwhile, the dependent variable of the study was the preventive behavior of diarrhea dehydration was measured in the form of knowledge, attitudes, and prevention of diarrhea dehydration. The statistical test used is the Wilcoxon Sign Rank Test <0.05. Dehy Pro significantly affected maternal behavior by increasing knowledge (p<0.000), attitude (p>0.000), and prevention of diarrhea dehydration (p<0.000). Dehy Pro can be an effective health promotion effort in reducing the number of diarrhea dehydration in children under five through increasing knowledge and the role of parents to take steps to prevent dehydration due to diarrhea.